Radiomics modelling in rectal cancer to predict disease-free survival: evaluation of different approaches. Issue 10 (23rd August 2021) - Tibermacine, H; Rouanet, P; Sbarra, M; Forghani, R; Reinhold, C; Nougaret, S
Abstract: Background: Radiomics may be useful in rectal cancer management. The aim of this study was to assess and compare different radiomics approaches over qualitative evaluation to predict disease-free survival (DFS) in patients with locally advanced rectal cancer treated with neoadjuvant therapy. Methods: Patients from a phase II, multicentre, randomized study (GRECCAR4; NCT01333709) were included retrospectively as a training set. An independent cohort of patients comprised the independent test set. For both time points and both sets, radiomic features were extracted from two-dimensional manual segmentation (MS), three-dimensional (3D) MS, and from bounding boxes. Radiomics predictive models of DFS were built using a hyperparameters-tuned random forests classifier. Additionally, radiomics models were compared with qualitative parameters, including sphincter invasion, extramural vascular invasion as determined by MRI (mrEMVI) at baseline, and tumour regression grade evaluated by MRI (mrTRG) after chemoradiotherapy (CRT). Results: In the training cohort of 98 patients, all three models showed good performance with mean(s.d.) area under the curve (AUC) values ranging from 0.77(0.09) to 0.89(0.09) for prediction of DFS. The 3D radiomics model outperformed qualitative analysis based on mrEMVI and sphincter invasion at baseline ( P = 0.038 and P = 0.027 respectively), and mrTRG after CRT ( P = 0.017). In the independent test cohort of 48 patients, at baseline and after CRT the AUC ranged from 0.67(0.09) to 0.76(0.06). All three models showed no difference compared with qualitative analysis in the independent set. Conclusion: Radiomics models can predict DFS in patients with locally advanced rectal cancer. Abstract : Radiomics may help predict disease-free survival in patients with locally advanced rectal cancer, at baseline and after neoadjuvant therapy. Radiomics may allow patient stratification before treatment initiation, and eventually for further adaptation of treatment after chemoradiotherapy